TELAAH ATAS FIQH AL-AQALLIYAT SYEKH YUSUF AL-QARDHAWI - Amir Sahidin (An Natiq, 2022)
In responding to the anxiety of Muslim minority communities in the West who are faced with dilemma choices. On the one hand, they are required to obey the teachings of Islam, but on the other hand they are faced with the reality of how difficult it is to practice Islamic teachings according to the guidance of the majority of Muslims. Therefore, Sheikh Yusuf al-Qardhawi initiated Fiqh al-Aqalliyat which can be a guide for Muslim minorities in the West. However, there are some Muslim scholars who use Fiqh al-Aqalliyat as a justification for shifting ushul fiqh towards maqashid al-syari'ah, even though both are very important to produce beneficial laws that do not come out of the Shari'a. For this reason, this article will examine the Fiqh of al-Aqaliyat Sheikh Yusuf al-Qardhawi. With literature-type research, it can be concluded, Sheikh al-Qardhawi is very concerned with the realization of benefits for humans which is the core of maqashid al-syari'ah. This can be seen from the basis of the arguments and foundations of Fiqh al-Aqaliyat, as well as the existence of important principles in ijtihad. All of this shows the balance of postulates with textual nash that are often used in ushul fiqh, and contextual maqashid al-syari'ah.